Legal Review of Evidence in The Crime of Defamation on Social Media - Agus Sugiarto (Journal of Social Research, 2025)
The development of social media has become part of everyday life, making it easier for individuals to express opinions, share information, and interact more widely and quickly. However, this convenience also creates legal challenges, one of which is the increase in defamation cases in the digital realm. Defamation on social media is a criminal offense that can harm individuals and institutions, but proving it is not easy. This research aims to analyze the legal aspects related to proof in the criminal act of defamation on social media. The research method used is normative research with data collection through literature study. The collected data is then analyzed with the stages of data filtering, data presentation, and conclusion drawing. The results show that evidence in the crime of defamation on social media refers to Article 27 paragraph (3) of the ITE Law as well as Articles 310 and 311 of the Criminal Code, with evidence regulated in Article 184 of the Criminal Procedure Code, including witness testimony, experts, letters, instructions, and testimony of the defendant. Digital forensics has an important role in ensuring the validity of electronic evidence, such as recorded conversations, screenshots, or metadata, to reveal the perpetrator's digital footprint and ensure data integrity. In addition, prosecutors must prove the element of intent (mens rea) to ensure that the posts were intended to defame and not merely criticize or a legitimate form of freedom of speech.